2014
DOI: 10.3390/nu6114794
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol and Its Metabolite, Isorhapontigenin, Induce SIRT1 Expression in THP-1 Human Monocytic Cell Line

Abstract: Piceatannol is a phytochemical that is present in large amounts in passion fruit (Passiflora edulis) seeds, and is an analog of resveratrol. Recently, the absorption and metabolism of piceatannol were investigated in rats, and isorhapontigenin, O-methyl piceatannol, was detected as a piceatannol metabolite in rat plasma. To elucidate the function of piceatannol and its metabolites, we investigated the expression of sirtuin 1 (SIRT1) in THP-1 monocytic cells after treatment with piceatannol and its metabolites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 28 publications
0
46
0
2
Order By: Relevance
“…The chemical profile of PFSE was previously reported. 13,15) The concentration of piceatannol was measured using HPLC analysis as previously described, 14) and this powder contained piceatannol (94.9 µg/mg) as a major polyphenol. PFSE was dissolved with 0.5% CMC containing 2 mg/mL or 10 mg/mL piceatannol within 3 h before administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical profile of PFSE was previously reported. 13,15) The concentration of piceatannol was measured using HPLC analysis as previously described, 14) and this powder contained piceatannol (94.9 µg/mg) as a major polyphenol. PFSE was dissolved with 0.5% CMC containing 2 mg/mL or 10 mg/mL piceatannol within 3 h before administration.…”
Section: Methodsmentioning
confidence: 99%
“…Although piceatannol shows activities similar to resveratrol, its levels in plants are significantly lower than those of resveratrol, 12) and it has therefore received far less research attention. We previously found that passion fruit seeds have a high piceatannol content, 13) and that piceatannol displays various properties such as sirtuin induction activity, 14) vasorelaxant effect, 15) upregulation of endothelial nitric oxide synthase expression, 16) promotion of collagen synthesis, inhibition of melanogenesis, 13) and protection of the skin from UVB irradiation. 17) Piceatannol shows much higher activity than resveratrol in some cases 13,16) ; however, its effects on metabolic syndrome remain unknown.…”
Section: )mentioning
confidence: 99%
“…The amount of Eresveratrol in grape skin is approximately three times higher than in pulp (Babazadeh et al 2017). Among the analysed edible berries, the highest concentration of stilbenes was found in the seeds of passion fruit (Passiflora edulis) (Kawakami et al 2014) by applying 80% EtOH as the solvent for extraction. However, the highest concentration of E-resveratrol in the skin has been found in table grapes (Vitis vinifera L.) (Ragab et al 2006) Table 2.…”
Section: Isolation and Identification Of Stilbenes In Edible Berriesmentioning
confidence: 95%
“…Many analytical methods with various detection techniques are reported for the separation and identification of individual stilbenes in edible berries, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Vrhovsek et al 2012), liquid chromatography-mass spectrometry (LC-MS) (Može et al 2011), liquid chromatography with dual detection by a photodiode array and quadrupole time-of-flight mass spectrometry (LC-PDA-QTOF/MS) (Samoticha et al 2017), high-pressure liquid chromatography-mass spectrometry (HPLC-MS) (Bavaresco et al 2002;Jiang et al 2012;Kiselev et al 2017), high-pressure liquid chromatography with diode array detection (HPLC-DAD) (Bavaresco et al 2002;Sun et al 2006;Vilanova et al 2015;Guerrero et al 2010aGuerrero et al , 2016, high-pressure liquid chromatography with UV detection (HPLC-UV) (Vincenzi et al 2013;Kawakami et al 2014;He et al 2009a), ultra-high-pressure liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC/QTOF/MS) (Flamini et al 2016;De Rosso et al 2016), ultra-performance liquid chromatography with dual detection by a photodiode array and fluorescence detectors (UPLC/DAD/FL) (Samoticha et al 2017), ultra-performance liquid chromatography with dual detection by a diode array and tandem quadrupole mass spectrometry (UPLC/ DAD/TQD) (Guerrero et al 2010a), gas chromatography-mass spectrometry (GC-MS) (Ragab et al 2006;Viñas et al 2009Viñas et al , 2011, gas chromatographymass spectrometry with selected ion monitoring (GC-MS SIM) (Rimando and Cody 2005), gas-liquid chromatography with flame ionization detection (GLC-FID) (Moriartry et al 2001), capillary electrophoresis (CE) (Ehala et al 2005) and high-speed counter-current chromatography (HSCC) (He et al 2009b). Various methods are used for analyses of stilbenes contents in the edible berries are different which could also contribute to the observed variability in the published results.…”
Section: Isolation and Identification Of Stilbenes In Edible Berriesmentioning
confidence: 99%
“…[7][8][9] Additionally, piceatannol (3,4,3′,5′-tetrahydroxy-trans-stilbene) has recently attracted much attention. [10][11][12] A recent report indicates that piceatannol and its metabolite, isorhapontigenin, induce expression of sirtuin 1 in THP-1 human monocytic cell line. 10) In addition to having similar biological activities to resveratrol, [10][11][12] piceatannol not only exerts positive effects on human dermal cells through the inhibition of melanogenesis and synthesis of collagen, but also exhibits vasorelaxant effects in rat thoracic aorta.…”
mentioning
confidence: 99%